Transcriptomic signatures in peripheral CD4+T-lymphocytes may reflect melanoma staging and immunotherapy responsiveness prior to ICI initiation - Palli, Eleni; Lavigne, Matthieu; Verginis, Panagiotis; Alissafi, Themis; Anastasopoulou, Amalia; Lyrarakis, Georgios; Kirkwood, John M.; Gogas, Helen; Ziogas, Dimitrios C. (Frontiers in Immunology, 2025)
Background and purposePromoting adaptive immunity with ICIs has drastically improved melanoma prognosis, but not for all patients. Some cases relapse in the first few months, while others keep durable benefit, even after immunotherapy discontinuation. To identify cellular/molecular signatures in peripheral blood that could differentiate advanced from metastatic melanoma and predict dynamics for primary/secondary immune escape, we examined 100 consecutive patients with stage III/IV melanoma scheduled to start ICIs.Materials and methodsAt melanoma diagnosis, a multiparameter flow cytometric analysis and purification scheme using standard conjugated antibodies were performed for all individuals prior to ICI initiation. In each stage(III/IV) according to their RFS/PFS, we retrospectively selected the cases with the clearest clinical outcomes and focused our analysis on the extreme responders(n=7) and non-responders(n=7) to characterize the transcriptomes of circulating CD4+T-cells by bulk RNA-seq, Differential Expression Analysis(DEA)and Gene Ontology(GO)enrichment analysis. Based on our selected patient cohort, we examined for differentially expressed genes(DEGs)and key-pathways that appear preferentially activated in stage III vs. IV melanoma, and in long vs. short immunotherapy responders.ResultsAlthough circulating immune-cells did not numerically differ in both sets of analysis(staging and ICI responsiveness), DEA and GO data showed that patients could be clustered separately, identifying 189vs.92 DEGs in stage IV/III and 101vs.47 DEGs in early progressors/long responders. These DEGs were functionally implicated in distinct pathways. For metastatic cases: inflammatory response(logp-value=-9.2:ADGRE5/2,CYBA,GRN,HMOX1,IRF5,ITGAM), adaptive immunity(logp-value=-7.7:CD1C,CD74,CYBB,NCF2,CTSA,S100A8/9,BCL3,FCER1G), T-cell activation(logp-value=-6.3:BCL3,CD1C,CD74,FCER1G,FGL2)and lipid metabolism/catabolism(logp-value=-2.5/-2.6:ARF3,GPX1,MVD,OCRL,PCCB,CTSA,PNPLA2,NAGLU,GBA2,ABHD4); while in early-progressors to ICIs: immune effector processing(logp-value=-13.7:BCL6,FGR,HLA-DQA1/DQB1,HLA-DRA,HLA-DRB1/DRB5,NKG7,SLC11A1,TYROBP,SPON2,HAVCR2),PD-1(logp-value=-10.2:HLA-DQA1/DQB1,HLA-DRA,HLA-DRB1/DRB5)and IFN signaling(logp-value=-8.5: HLA-DQA1/DQB1,HLA-DRA,HLA-DRB1/DRB5,NCAM1,IFITM3),positive regulation of T-cell activation(logp-value=-7.7:BCL6,HLA-DQA1/DQB1,HLA-DRA,HLA-DRB1/DRB5,SASH3,HAVCR2)and CD28 co-stimulation(logp-value=-10.3:HLA-DQA1/DQB1,HLA-DRA,HLA-DRB1/DRB5), supporting an immune-mediated behavior.ConclusionsSpecific pathways and marker genes in the peripheral CD4+T-cells may predetermine melanoma staging and immunotherapy resistance.